PENGARUH LAYANAN DAN KONSULTAN KOMUNIKASI TERHADAP MINAT PESERTA DIDIK PADA LEMBAGA PIONEER CLASS MAKASSAR 2022 - Akbar , A. Ali; Majid , Abd; Muttaqin Mustari , Andi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Educational institutions that have good quality of service and communication consultants are the dream of parents to support their children's education, and have competent teaching staff and good supporting books. This study aims to analyze the effect of educational services and communication consultant in pioneer class institutions and find out the relationship between educational services and Communication consultants and student interests. The method is carried out with a quantitative approach using multiple linear regression analysis. The sample taken from this study was 40 respondent. One of the factors that causes educational services to be less influential is the lack of services that meet the needs of goods and services in the Makassar Pioneer Class Institution. Communication Consultants have a relationship and influence on student interests, so it can be concluded that there is a significant influence between Communication Consultants on student interests. This is motivated by the factor of interpersonal communication that occurs in communication consultants.